2020
DOI: 10.1007/s40858-020-00375-4
|View full text |Cite
|
Sign up to set email alerts
|

Friend or foe? Relationship between ‘Candidatus Liberibacter asiaticus’ and Diaphorina citri

Abstract: Interactions between insects and plant pathogens have been more enthusiastically studied in the recent decade, especially those relationships which takes the insects as vectors. The spectrum of these interactions ranges from mutualistic to pathogenic. The length of the co-evolutionary process will determine whether a microorganism shares a friend or a foe relationship with its host, and a friendship connection is frequently observed if the coexistence is longer. This review updates knowledge about the morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 154 publications
1
22
0
3
Order By: Relevance
“…Despite this, the host-switching, long-term relationship between the ACP population and CLas-infected plants, could result in a more stable association between these organisms [35]. ACP nymphs present an attenuated bacterial response that allows efficient CLas colonization [27,36].…”
Section: Generations Total Number Of Samplesmentioning
confidence: 99%
“…Despite this, the host-switching, long-term relationship between the ACP population and CLas-infected plants, could result in a more stable association between these organisms [35]. ACP nymphs present an attenuated bacterial response that allows efficient CLas colonization [27,36].…”
Section: Generations Total Number Of Samplesmentioning
confidence: 99%
“…Phytoplasma) are dependent on insect vectors for plant-to-plant transmission (Orlovskis et al 2015). Some of them are able to directly or indirectly affect both plant (e.g., nutritional profile, chemical signaling) and vector insect (e.g., behavior, longevity, fecundity) (Bendix and Lewis 2018;Dermastia 2019;Eigenbrode et al 2018;Galdeano et al 2020;Gross 2016;Mauck et al 2016;Perilla-Henao and Casteel 2016;Shikano et al 2017;Stout et al 2006;Tamborindeguy et al 2017). While many research results on ecological interactions of plant viruses or Ca.…”
Section: Introductionmentioning
confidence: 99%
“…HLB is caused by Candidatus Liberibacter spp., a fastidious phloem-restricted bacterium transmitted by leafhoppers, and is characterized by a long incubation period of three months to multiple years before symptoms are visible (Manjunath et al, 2008;Flores-Sánchez et al, 2017;Canale et al, 2020). The Asian psyllid Diaphorina citri is the most efficient vector and transmits the pathogen in a circulative-propagative (persistent) transmission cycle (Manjunath et al, 2008;Hall et al, 2013;Torres-Pacheco et al, 2013;Keremane et al, 2015;Galdeano et al, 2020). According to Canale et al (2017), the psyllids were able to transmit the pathogen for up to 5 weeks after a 14-day acquisition access period as nymphs.…”
Section: Huanglongbing (Hlb)mentioning
confidence: 99%
“…According to Canale et al (2017), the psyllids were able to transmit the pathogen for up to 5 weeks after a 14-day acquisition access period as nymphs. The psyllid is capable of acquiring the pathogen after feeding for 15 to 30 minutes and remains infective throughout their life (3 to 4 months) (Hall et al, 2013;Galdeano et al, 2020); transovarian transmission has been reported only in the African psyllid Trioza erytreae (Manjunath et al, 2008). Gottwald et al (2008) analyzed the effect of contagion by psyllids at close range, on the global dispersal pattern of the disease over time, finding that the infection of trees occurs mainly by psyllids that come from contaminated tree blocks not close to uninfected trees, and not by psyllids from nearby orchards.…”
Section: Huanglongbing (Hlb)mentioning
confidence: 99%